Policy implications for gaps in traditional plastic waste material flow analysis: Palmerston North, New Zealand - Farrelly, Trisia; Chitaka, Takunda Yeukai (Frontiers in Sustainability, 2023)
The Basel Plastic Waste Amendments reflect growing global concern about the illegal plastic waste trade as waste colonialism. Comprehensive analyses of plastic waste material sources, pathways, and fates are needed for effective plastic waste trade policy. Plastics waste flows from Palmerston North, New Zealand to Malaysia highlight gaps in plastic waste trade policies. The authors recommend strengthening New Zealand’s national waste policy framework and the Basel Convention’s Plastics Amendments by basing policy responses on transboundary plastic waste material flow analyses, establishing harmonised definitions including ‘recyclable’ and ‘environmentally sound recycling’; regulating contamination thresholds and container inspections, and waste trade traceability, transparency, compliance, enforcement, and remediation; reclassifying fluorinated polymers and thermosets as ‘hazardous’; and prioritising principles of prevention and proximity.